Unsociability and Psychological and School Adjustment in Chinese Children: The Moderating Effects of Peer Group Cultural Orientations. (February 2023) - Zhao, Siman; Liu, Mengting; Chen, Xinyin; Li, Dan; Liu, Junsheng; Liu, Shihong
This study examined the moderating effects of cultural orientations of peer groups on the relations between unsociability and psychological and school adjustment in Chinese children. Participants included 1, 092 students (527 boys, M age = 12.21 years) in the sixth grade in elementary schools. Data on individualistic and collectivistic cultural orientations, unsociability, and adjustment were obtained from multiple sources including peer nominations, teacher ratings, self-reports, and school records. Using the Social Cognitive Map method, 193 peer groups were identified. Among the results, unsociability was negatively associated with peer preference and academic achievement in groups low on individualistic orientation but not in groups high on individualistic orientation. Unsociability was also negatively associated with peer preference more strongly in groups with higher scores of collectivistic orientation. The results suggested that, in general, unsociable children performed better in social and academical areas in more individualistically oriented groups and less collectivistically oriented groups. The cultural context of peer groups may play a significant role in shaping social and school adjustment of unsociable children.